2008
DOI: 10.2175/106143007x221085
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification with Carbon Addition—Kinetic Considerations

Abstract: The Blue Plains Advanced Wastewater Treatment Plant (Washington, D.C.) uses methanol as an external carbon source in a postdenitrification process, to achieve low effluent total nitrogen concentrations. This becomes more difficult in winter, at lower mixed liquor temperatures and higher flows, as a consequence of the kinetic behavior of the methanol-utilizing heterotrophs. The paper reports on an experimental batch test study conducted on Blue Plains postdenitrification sludge to investigate (1) the maximum sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…The use of ethanol with methanol and acetate grown biomass generated SDNRs of 7.2 and 4.7 mg NO 3 -N/g VSS/hr, respectively. The SDNR of ethanol with methanol grown biomass is similar to the SDNR of methanol with methanol grown biomass, suggesting that the methanol grown biomass can use ethanol, nearly as well as methanol, confirming the work by Dold et al (2007) and Nyberg et al (1996). The use of acetate with ethanol grown biomass produced the highest SDNR of 18.9 mg NO 3 -N/g VSS/hr.…”
Section: Ex Situ Specific Denitrification Rate Testssupporting
confidence: 73%
“…The use of ethanol with methanol and acetate grown biomass generated SDNRs of 7.2 and 4.7 mg NO 3 -N/g VSS/hr, respectively. The SDNR of ethanol with methanol grown biomass is similar to the SDNR of methanol with methanol grown biomass, suggesting that the methanol grown biomass can use ethanol, nearly as well as methanol, confirming the work by Dold et al (2007) and Nyberg et al (1996). The use of acetate with ethanol grown biomass produced the highest SDNR of 18.9 mg NO 3 -N/g VSS/hr.…”
Section: Ex Situ Specific Denitrification Rate Testssupporting
confidence: 73%
“…All Rights Reserved. 274 heterotrophic bacteria participating in the process (Grabinska-Loniewska et al, 1985;Dold et al, 2008). Methanol is the most widely used external carbon source for denitrification since it is low in cost (Mokhayeri et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies indicate that the maximum specific growth rate of methanol-utilizing organisms is low, 1.3/day at 20ºC, and highly temperature dependent (Nichols et al, 2007;Dold et al, 2008). Thus, when temperatures decrease during the winter, it is difficult for wastewater treatment (WWTP) plants adding methanol as the primary source of external carbon to achieve the required effluent total nitrogen limitations noted above without providing substantial reactor capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The Espoo modelling work also helped optimize plant operation, and an important finding was to not dose carbon to the last anoxic compartment in order to avoid unnecessary carryover of RBCOD to the aerobic reactors. Also, because methylotrophs are very temperature-sensitive (Dold et al 2007), it was concluded that the yearly average nitrogen removal rate target of 70% could be more cost-effectively met by running the plant at 80% nitrogen removal in the summer and 60% nitrogen removal in winter. Finally, models play a critical role at facilities with low discharge limits such as the Western Branch WWTP in Upper Marlboro, Maryland,…”
Section: The Value Of Modellingmentioning
confidence: 99%